Icing and De-icing under Centrifugal Load in DLR’s Whirl Tower Facility - Kalow, S.; Bartels, R.; Schneider, O.; Sahyoun, D.; Keimer, R. (My University, 2023)
The paper presents current DLR activities focusing on experimental icing investigations within the InTEnt-H project. The aim of the project is to investigate innovative de-icing and anti-icing technologies for small and medium-weight helicopters, for which no such technologies exist to date, and to demonstrate the effective-ness of these systems in a suitable test facility. For this purpose, the rotor test facility at DLR in Brunswick will be converted into an icing facility that is unique in Europe and will allow the generation of atmospheric icing conditions in compliance with EASA requirements. Furthermore, the progress of the first test campaign of the project will be reported. The focus will be on the first icing tests as well as on the de-icing of a rotating demonstration blade by means of electrically operated heating foils and a waste-heat technology.
Keywords: Test & Evaluation